The Diffusion of Innovation on the Village’s Population Administration Service (Pesta Dansa) in Sukoharjo Village, Sukoharjo District, Wonosobo Regency - Ridwan Kurnia Fajar; Sakir Sakir (Universitas Muhammadiyah Ponorogo, 2022)
This research aims to review the diffusion of innovation on “Pesta Dansa” (Pelayanan Administrasi Kependudukan di Desa) or the Village’s Population Administration Service in Sukoharjo Village, Sukoharjo District, Wonosobo Regency. The involved parties in this research are including the Population and Civil Registration Service of Wonosobo Regency, the Sukoharjo Village’s Government, as well as the community receiving the “Pesta Dansa” innovation service. This research uses a mixed method combined with a case study approach. The results show that the diffusion of “Pesta Dansa” innovation in Sukoharjo Village has been running well. This is evidenced by the successful implementation of “Pesta Dansa” innovation in Sukoharjo Village, by referring to 5 indicators proposed by Roger in the diffusion of innovation theory, including; 1) Knowledge, the“Pesta Dansa” innovation has the suitability of benefits to the problem of population administration services in Sukoharjo Village; 2) Persuasion, the success of Sukoharjo Village’s government in introducing the “Pesta Dansa” innovation to the community; 3) Decision, the acceptances and supports from the Sukoharjo Village’s government as well as the community towards the implementation of “Pesta Dansa” innovation; 4) Implementation, the success of Sukoharjo Village’s government in applying the “Pesta Dansa” innovation to the community; 5) Confirmation, the community’s assessment and evaluation survey results regarding the implementation of “Pesta Dansa” innovation by the Sukoharjo Village’s government.